Root Canal Morphology of Mandibular Canine in an Iranian Population: A CBCT Assessment - Soleymani, Ali; Namaryan, Nafiseh; Moudi, Ehsan; Gholinia, Ali (Iranian Endodontic Journal, 2016)
Introduction: The present study was conducted to assess the morphology of mandibular canines using cone-beam computed tomography (CBCT) in a north Iranian population. Methods and Materials: For the morphological assessment of mandibular canines, 150 CBCT images taken from patients for different reasons were used. The mandibular canines were examined in sagittal, coronal and axial dimensions. The canal pattern, number of roots/canals, the tooth length, the orientation of the roots and the position of the apical foramina were evaluated and the effect of gender on each variable was assessed. The obtained data were analyzed using the Chi-square and student’s t-tests. Results: According to the Vertucci’s criteria, the most common pattern was type I morphology (89.7%), followed by types III (5.7%), II (3.7%) and V (1%). No significant differences were observed between the male and female patients in terms of canal type (P>0.05). Gender difference is a factor which affected the root length and the number of mandibular canine root and root canal. There were 296 single-root and four double-root canines. The double-root canines and mandibular canine with two canals were significantly more common among men than women (P=0.00). The apical foramen was laterally positioned in 68.3% and centrally in 31.7% of the cases, and the root curvatures were mostly oriented toward the buccal region. No significant statistical difference was observed for mentioned parameters in right and left half of the jaw. Conclusion: Due the diverse morphology and the potential presence of a second mandibular canine among Iranians, dentists should perform endodontic treatments with greater care. CBCT is an accurate tool for the morphological assessment of root canals. Keywords: Canine; Cone-Beam Computed Tomography; Root Canals